THE EFFECT OF DISCOVERY LEARNING MODEL TO IMPROVE UNDERSTANDING OF EXPOSITION TEXT IN GRADE VIII STUDENTS AT MTSN 3 KARAWANG: PENGARUH MODEL DISCOVERY LEARNING UNTUK MENINGKATKAN PEMAHAMAN TEKS EKSPOSISI PADA SISWA KELAS VIII DI MTSN 3 KARAWANG - Julaeha; Daman Huri; Een Nurhasanah (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
This study aims to evaluate the impact of the Discovery Learning model in enhancing students' understanding of expository texts in the eighth grade of MTs Negeri 3 Karawang. The method used is quantitative research with a quasi-experimental design, involving two groups: the experimental group taught using the Discovery Learning model, and the control group taught using conventional methods. The data for this study was collected through pretests and posttests and analyzed using statistical tests such as the N-Gain test and t-test. The results showed a significant improvement in the understanding of expository texts in the experimental group compared to the control group. The average posttest score of the experimental group was higher, at 87, compared to the control group, which only reached 41. This indicates that the use of the Discovery Learning model significantly increased student engagement in the learning process and their comprehension of expository texts. These findings provide important contributions to the development of more interactive and innovative teaching methods and can serve as a reference for teachers to improve the quality of Indonesian language learning. The study also highlights the importance of implementing student-centered learning strategies to maximize learning outcomes.